Significância dos impactos ambientais resultantes do processo construtivo de edificações – ferramenta para análise e estudo multicaso - Soares, Rafaela Guedes Lins (2017)
Environmental impacts, which alter the environment and result in the quality of life and well-being of society, can have their causes in the constructive process of buildings. This work presents the results of a research that had as objective to analyze the significance of the environmental impacts resulting from the construction process of three building works. Initially, it was necessary to know the causes of the environmental impacts in the different stages of the constructive process of buildings, as well as to identify these impacts, in order to evaluate their significance, through the criteria used in the method of Seiffert (2011). According to the said method, this significance can be: despicable, moderate and critical. The results showed that 83.78% of the identified environmental impacts represent moderate to critical significance, which is a worrying situation. This demonstrates that the environment is being polluted considerably by the construction industry due to the lack of environmental management and the wrong working method of the companies. The neglect of these companies in the face of environmental issues is notorious, since there is no control in the causes of environmental impacts, that is, there are no actions aimed at eliminating or minimizing them, thereby compromising the quality of life of society. .